IMPLEMENTASI KERJASAMA WAHID FOUNDATION DAN UN WOMEN DALAM PEMBERDAYAAN PEREMPUAN DI INDONESIA MELALUI PROGRAM PEACE VILLAGE - Batassya Ayunur, (2021)
International cooperation can be carried out not only between countries, but can also be carried out by non-state actors which include international organizations and non-governmental organizations that are able to provide greater influence and greater effectiveness in achieving the goals of a country. In this case, there is international cooperation between non-state actors that has been established, which is the collaboration between the Wahid Foundation as a non-governmental organization and UN Women as an international organization. The collaboration between the Wahid Foundation and UN Women in 2017 can be a proof that cooperation between non-state actors is needed in realizing the success of Indonesia's national goal in women's empowerment. It can be proven by how the RAN P3AKS which is a ratification of UN Resolution 1325 or the framework of the Women Peace Security agenda can be implemented in Indonesia through collaboration between the Wahid Foundation and UN Women in its program, Peace Village. The Peace Village program is a successful program in realizing women's empowerment in Indonesia by making various efforts to increase women's roles and contributions, develop women's leadership, and empower women's economy in various villages. It is due to the role of women is barely considered and women's empowerment has not been fully realized in Indonesia. Therefore, there is a need for cooperation between non-state actors to support increasing the role of women and realizing women's empowerment in Indonesia. This study explains how the collaboration between the Wahid Foundation and UN Women is established and how the performance or implementation of the Peace Village program in realizing women's empowerment in Indonesia. This research is guided by using several theories and concepts, which are the theory of International Cooperation, the theory of Neoliberal Institutionalism, and the Concept of Women's Empowerment. In the research method, the author uses a descriptive qualitative method of research.